More Than a Ligand: PD-L1 Promotes Oncolytic Virus Infection Via a Metabolic Shift That Inhibits the Type I Interferon Pathway - Hodgins, Jonathan James (Université d'Ottawa / University of Ottawa, 2023)
Targeting the PD-1/PD-L1 axis has transformed the field of immune-oncology. While conventional wisdom initially postulated that PD-L1 serves as the inert ligand for PD-1, an emerging body of literature suggests that PD-L1 has cell intrinsic functions in immune and cancer cells. In line with these studies, here we show that engagement of PD-L1 via cellular ligands or agonistic antibodies potently inhibits the type I interferon pathway in cancer cells. Hampered type I interferon responses in PD-L1-expressing cells resulted in enhanced infection with oncolytic viruses in cancer cells in vitro and in vivo. Consistently, PD-L1 expression marked tumour explants from cancer patients that were best infected by oncolytic viruses, indicating PD-L1 could be a biomarker for tumours that will best respond to oncolytic viruses. Mechanistically, PD-L1 suppressed type I interferon by promoting Warburg metabolism, characterized by enhanced glucose uptake and glycolysis rate. Lactate generated from glycolysis was the key metabolite responsible for inhibiting type I interferon responses and enhancing oncolytic virus infection in PD-L1 expressing cells. In addition to adding mechanistic insight into PD-L1 intrinsic function, this work suggests that PD-L1 has a broader impact on immunity and cancer biology besides acting as a ligand for PD-1.
Keywords: Cancer; Immunology